Trumpism, Immigration and Globalisation - Kaur, Arunajeet (2018)
President Donald Trump has intensified a debate about US national identity and American attitude towards migration since taking office a year ago. Trump’s first State of Union Address in January continues to reiterate tough curbs on immigration which is unsettling to both Americans and believers of globalisation.